Risk factors related to the positivity to Aedes aegypti mosquito in houses of the Municipal Polyclinic health area - Digna de la Caridad Bandera Jiménez; Patrick Moreau; Dennis Gonzáles Mustelier; Lázaro Ibrahim Romero García; Tania Leyva Miranda (Centro Provincial de Información de Ciencias Médicas, 2017)
A case and control study represented by 155 and 310 houses, respectively, to identify risk factors related to the positivity to Aedes aegypti mosquito in the area of the Municipal Polyclinic in Santiago de Cuba, was carried out during 2012. Among the risk factors there were: unprotected low deposits, unclean yards, likings, high deposits and others, about which the odds ratio, the population attributable reason and the etiologic fraction were obtained. It was concluded that such factors perpetuated the presence of the vector focuses in those homes of the aforementioned health area.